On Joachimsthal's theorems in Riemann-Otsuki space R - O3 - Yildirim Yilmaz, Munevver; Bektas, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2014)
In this paper we study the Joachimsthal theorem in Riemann-Otsuki space
Keywords: Riemann-Otsuki spaces; Frenet formula; curvature strip